A Preliminary Study of the Macrofauna of Sandy Shore and Mangrove Forest of the North East Coast of Langkawi - Harinder Rai, Singh; Amy Then Yee, Hui (Malaysian Journal of Science, 2005)
This study reports on the macrofauna (epifauna and infauna) of two sandy shores (Burau Bay and Tanjung Rhu) and a mangrove forest (Tanjung Rhu). A total of sixty taxa were recorded from both the sandy shores and the mangrove forest. Burau Bay Beach recorded 25 taxa, Tanjung Rhu mangrove forest recorded 23 taxa while Tanjung Rhu Beach recorded 22 taxa. Soil water salinity and pH was quite similar from the beach as well as the mangrove forest but there was appreciable difference between percent soil organic content from the beach habitats to that of the mangrove forest, being higher in the latter. The beach fauna mainly comprised of polychaetes, bivalves and gastropods while that of the mangrove forest was dominated by crustaceans and three species of gastropods.